Feeling empowered: Nursing students' experiences of work-family-school role conflicts - Seyed Saeed Najafi; Marzieh Momennasab; Banafsheh Tehranineshat (Elsevier, 2023)
Background: Nurses educating at postgraduate levels take the role of students besides their work- and family-related roles. However, this struggling experience of the nursing students has remained a little-discussed topic. Objectives: This research aimed to explore the experience of nursing students educating at postgraduate levels from work-family-school role conflicts. Methods: This study is a qualitative content analysis conducted on 11 nursing students of Master's and PhD programs at School of Nursing and Midwifery, Shiraz University of Medical Sciences, Shiraz, Iran. The study lasted from February to August 2020. The participants were selected using purposive sampling method and this procedure continued until data saturation. The data were collected by semi-structured in-depth individual interviews and analyzed by Graneheim and Lundman approach. Results: Feeling empowered was extracted from data as main theme with two categories including learning development (with three sub-categories) and role management (with four sub-categories). Conclusion: Despite experiencing work-family-school role conflicts, nursing students studying at postgraduate levels felt empowered through acquiring knowledge and improving professional and problem-solving skills. Moreover, they tried to manage their multiple roles using strategies such as proper planning and hard work for accomplishing tasks properly.